NUTRIENT CONTENT OF SOYBEAN MEAL FROM DIFFERENT ORIGINS BASED ON NEAR INFRARED REFLECTANCE SPECTROSCOPY - Budi Tangendjaja (Indonesian Agency for Agricultural Research and Development, 2020)
Near infrared reflectance spectroscopy (NIRS) has become common techniques to estimate chemical composition of feed ingredient for poultry. Two experiments were performed: first was to compare the capability of NIRS system from three laboratories (E, A and T) to measure nutrient composition of soybean meal (SBM); and the second was to evaluate nutrient composition and quality of 59 samples of SBM from Argentine, Brazil and US using NIRS from T-laboratory. Thirty samples of SBM was used in the first study and the result showed that all NIRS systems were able to estimate proximate, amino acids, metabolizable energy (ME) and carbohydrate components. The second experiment indicated that there were some differences in proximate composition (especially protein), total amino acids and digestible amino acids among SBM from different origins. Brazilian SBM had 2% higher protein and amino acid compared to US or Argentine SBM (P<0.05). However, US SBM had slightly higher ME (20 and 40 kcal kg-1) compared to Brazilian and Argentine SBM, respectively. ME is positively correlated with protein (0.50) and fat content (0.58) but negatively correlated with fiber (-0.74) and NSP (-0.61). Stepwise regression analysis demonstrated that ME can be estimated using equation ME (kcal kg-1) = 75.7 – 21.0 x Fiber + 87.4 x Fat + 32.9 x Protein + 17.6 x NFE with reasonable accuracy (R2 = 0.995). In conclusion NIRS can be used to estimate nutrient content of SBM. Brazilian SBM has higher protein and amino acids, but US SBM has slightly higher ME content.